The Interplay of Extrinsic and Intrinsic Motivational Factors on Teachers’ Continuance and Affective Commitment - Mañoza, Venus; Cruz, Yvonne (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to evaluate the motivational levels of junior high school teachers in Dumaguete City, focusing on extrinsic and intrinsic motivation and their affective and continuance commitment. A descriptive correlational survey was employed, and statistical analysis was performed using weighted mean, frequency distribution, percentage, Pearson r, and Kruskal–Wallis test. The findings indicate that teachers' extrinsic and intrinsic motivational levels are high. Additionally, their commitment to their job is also high in terms of affective and continuance commitment. The study found a strong significant relationship between motivational levels and affective commitment, while the relationship with continuance commitment was weak but still significant.